IMPLEMENTATION OF THE HOUSING AND BUILDING MAINTENANCE ACT AND THE PRINCIPLE OF SUSTAINABLE HOUSING: Upravljanje i održavanje zgradama - Lazic, Miroslav (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The society should pay special attention to management and maintenance of residential buildings in order to provide citizens with sustainable housing in accordance with European standards of quality housing, environmental standards, energy efficiency, cleanliness and safety, accessibility for people with special needs, protecting third parties from possible risks, etc. By adopting the Housing and Building Maintenance Act (HBM Act) in 2016 and declaring building maintenance a public interest, the Serbian legislator took a significant step towards providing legal conditions for resolving decades-old housing problems. The past decade of application of the HBM Act is an opportunity to analyze the implementation of this legislative act and draw attention to the need to introduce certain amendments. Sustainable housing development includes the improvement of citizens’ housing conditions, the preservation and improvement of the housing stock value (energy efficiency and living conditions by reducing negative impacts on the environment), as well as responsible professional management and maintenance of residential buildings by professional managers in order to create conditions for functional and safe housing. In addition to the legal personality of the owners of separate parts (condominium), housing communities have become legal entities with separate legal personality. In the author’s opinion, the advantages of professional management of residential building has been confirmed in practice. Thus, the paper emphasizes the need to amend the HBM Act in order to introduce provisions on the mandatory professional management and maintenance of residential buildings, risk insurance, and contractual regulation of mutual relations of the owners of separate parts (condominium).
Keywords: condominium; sustainable housing; professional management of residential buildings; building insurance; Housing and Building Maintenance Act RS